2002
DOI: 10.1210/jcem.87.4.8138
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Transdermal Dihydrotestosterone in the Aging Male: A Prospective, Randomized, Double Blind Study

Abstract: The objective of the study was to investigate the effects of dihydrotestosterone (DHT) gel on general well-being, sexual function, and the prostate in aging men. A total of 120 men participated in this randomized, placebo-controlled study (60 DHT and 60 placebo). All subjects had nocturnal penile tumescence once per week or less, andropause symptoms, and a serum T level of 15 nmol/liter or less and/or a serum SHBG level greater than 30 nmol/liter. The mean age was 58 yr (range, 50-70 yr). Of these subjects, 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
35
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…However, the lack of estrogenic activity of DHT could be regarded as an advantage in particular situations, such as gynecomastia, where estrogenic activity of T should be avoided. Concerns on the use of DHT for Tth derives also from its putative prostate‐stimulating effect, which however was not confirmed in the few trials published so far ([136], EBMl1a). DHT is available in some countries as a 2.5% transdermal preparation and in others as an orally active 1‐methyl derivative, mesterolone, which is converted by the liver to DHT.…”
mentioning
confidence: 99%
“…However, the lack of estrogenic activity of DHT could be regarded as an advantage in particular situations, such as gynecomastia, where estrogenic activity of T should be avoided. Concerns on the use of DHT for Tth derives also from its putative prostate‐stimulating effect, which however was not confirmed in the few trials published so far ([136], EBMl1a). DHT is available in some countries as a 2.5% transdermal preparation and in others as an orally active 1‐methyl derivative, mesterolone, which is converted by the liver to DHT.…”
mentioning
confidence: 99%
“…As DHT is implicated in the development of benign prostatic hyperplasia (BPH) and prostate cancer, high DHT blood levels have traditionally been regarded as undesirable. Furthermore, three DHT gel studies did not report any increase in PSA levels, prostate volume or symptoms (de Lignieres, 1993;Ly et al, 2001;Kunelius et al, 2002). Studies with scrotal testosterone patches providing a long-term outcome with high DHT blood levels over a period of several years, do not indicate any risk of prostatic hyperplasia or cancer, although they involve only a small number of patients (Behre et al, 1999).…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, three DHT gel studies did not report any increase in PSA levels, prostate volume or symptoms (de Lignieres, 1993;Ly et al, 2001;Kunelius et al, 2002). Further, the androgen physiological mechanisms of the prostate are geared to maximise androgen effects, first by its high density of T receptors, and second by its high degree of conversion of T to DHT (Wilson, 1996), resulting in higher intraprostatic DHT levels than serum DHT levels and higher levels of intraprostatic DHT than levels of intraprostatic T. This could potentially explain why an elevation of peripheral DHT levels has no impact on the prostate itself, also apparent from studies that used DHT itself for androgen treatment which found no effect on the prostate (de Lignieres, 1993;Ly et al, 2001;Kunelius et al, 2002). In one study, even a 15% decrease of prostate volume was detected (de Lignieres, 1993), and this is possibly due to the following mechanism: DHT suppresses LH and FSH levels, resulting in lower endogenous T production which in turn leads to diminished aromatisation of testosterone to oestradiol.…”
Section: Discussionmentioning
confidence: 99%
“…40Y42 Mood enhancement and improved well-being figure prominently in anecdotal reports and uncontrolled clinical trials, 16,41 but these have not been consistently demonstrated in placebo-controlled studies of either hypogonadal 17,40,43 or eugonadal 42,44,45 men. The body of evidence suggests that administration of exogenous testosterone has consistent positive effects on libido and energy, which seem to be greatest in the setting of hypogonadism (ie, testosterone replacement).…”
Section: Discussionmentioning
confidence: 99%